Synthesis and Insecticidal/Fungicidal Activities of Triazone Derivatives Containing Acylhydrazone Moieties - Peipei Cui; Yan Yang (Molecules)
A series of novel triazone derivatives containing aldehyde hydrazone or ketone hydrazone moieties were designed, synthesized and their biological activities were investigated against Aphis craccivora, Culex pipiens pallens, Helicoverpa armigera, Ostrinia nubilalis, Mythimna separata and 14 Kinds of fungi. Most of the aldehyde hydrazone exhibited excellent insecticidal activities against A. craccivora. In particular, the aphicidal activities of compounds 3t (35%) and 3w (30%) were equivalent to pymetrozine (30%) at 5 mg/kg. The aphicidal activities of derivatives 3p, 3u, 3y, 5g, 5i, 5l, 5q and 5u against C. pipiens pallens were higher than that of pymetrozine. Compound 3u (100%) exhibited good larvicidal activities against C. pipiens pallens at 0.25 mg/kg. Most derivatives exhibited broad-spectrum fungicidal activities against 14 kinds of plant fungi at 50 mg/kg. Thirty-nine compounds exhibited a more than 50% inhibition rate against Physalospora piricola. Compounds 3h, 3t and 3w were expected to be the leading structure for the development of new triazone insecticides agents.